Effect of a honey-sweetened beverage on muscle soreness and recovery of performance after exercise-induced muscle damage in strength-trained females - Hadis Hemmati; Walaa Jumah Alkasasbeh; Mohammad Hemmatinafar; Mohsen Salesi; Sepideh Pirmohammadi; Babak Imanian; Rasoul Rezaei (Frontiers in Physiology)
BackgroundThis study explores a novel approach to mitigating delayed-onset muscle soreness (DOMS), a common issue among strength-trained females. By investigating the potential of a honey-sweetened beverage, which contains anti-inflammatory properties, we aim to enhance muscle recovery after exercise-induced muscle damage (EIMD).MethodA randomized, cross-over, placebo-controlled, and double-blinded study was conducted with sixteen female strength athletes. Firstly, the baseline measurements were recorded, and participants were randomly divided into two conditions: honey-sweetened beverage (HSB; 70 g of honey in 250 mL water with a concentration of 28%) and placebo (PLA; 250 mL of water with 70 g of artificial sweetener). The HSB and PLA were consumed 90 min before the EIMD started (200 vertical jumps with 10% body-weighted vests). Recovery monitoring of performance indicators and DOMS was performed after EIMD. The results of wall-sit, V-Sit and reach flexibility test (VSFT), vertical jump height (VJH), pressure pain threshold (PPT), and one repetition maximum (IRM) tests were recorded 48 h after EIMD. Also, DOMS was recorded using the visual analog scale (VAS) before the start of the test and immediately, 12, 24, and 48 h after EIMD. A one-week interval was considered a washout period for each condition. The collected data were analyzed by repeated measures of ANOVA and Bonferroni post hoc test and dependent t-test at P ≤ 0.05 level.ResultsCompared to PLA, HSB ingestion improves wall-sit performance (p = 0.003), 1RM (p = 0.019), and RPE (p = 0.003) after EIMD. However, no significant differences were observed between BL, PLA, and HSB in VJH (p = 0.384), VSFT (p = 0.840), and PPT (p = 0.151) after EIMD. Furthermore, HSB, compared to PLA, considerably decreased the values of DOMS immediately, 12, 24, and 48 h after EIMD (p < 0.05).ConclusionOur findings illustrated that ingesting HSB in strength-trained females can be a helpful strategy for improving recovery indicators such as muscle strength, endurance, and muscle soreness after EIMD.